Stakeholder Collaboration in Increasing Community Participation and Independence in the Mina Padi Tourism Village in Cilongok District, Banyumas Regency - Ahmed Benjamin Agung; Nita Triana (Postgraduate, State Islamic University Prof. K.H. Saifuddin Zuhri Purwokerto, 2025)
This study aims to analyze the forms and roles of inter-stakeholder collaboration in efforts to increase community participation and independence in the management of the Mina Padi Tourism Village in Cilongok District, Banyumas Regency. The research approach used was descriptive qualitative, with data collection techniques including in-depth interviews, observation, and documentation studies. The stakeholders involved included the village government, tourism awareness groups (Pokdarwis), local communities, academics, and the private sector. The results show that the multi-stakeholder collaboration that has been established contributes to increased community participation in planning, implementation, and evaluation of agriculture-based tourism activities (rice). In addition, synergy among stakeholders encourages economic independence through strengthening community capacity, tourism product innovation, and business diversification based on local potential. However, this study also found that the sustainability of collaboration still faces challenges in coordination, role distribution, and consistency of support from external parties. Therefore, a more structured strategy is needed to strengthen networks and collaborative governance to ensure sustainable and competitive development of the Mina Padi Tourism Village.